Direct and indirect effects of nutritional status, physical function and cognitive function on activities of daily living in Japanese older adults requiring long‐term care. Issue 4 (12th November 2013) - Kamo, Tomohiko; Nishida, Yuusuke
<x xml:space="preserve">Abstract</x> Aim To identify the direct and indirect effects of nutritional status, physical function, and cognitive function on activities of daily living in Japanese older adults requiring long‐term care. Methods In total, 179 participants aged ≥65 years who were eligible for long‐term care insurance (mean age 85.5 ± 7.8 years) were recruited for this study. Nutritional status (Mini Nutritional Assessment, Short Form) and physical function (Short Physical Performance Battery) were examined. Activities of daily living, cognitive function and frailty were assessed using the Barthel Index, Mini‐Mental State Examination and Clinical Frailty Scale, respectively. Path analysis was used to determine relationships between these factors and the activities of daily living. Results For Japanese older adults requiring long‐term care, pathways were modeled for nutritional status, physical function and the activities of daily living. The total effect of nutritional status was 0.516 (P < 0.001). The indirect effect of nutritional status through physical function on the activities of daily living was 0.458 (P < 0.001). Finally, no significant direct effect of nutritional status on activities of daily living was observed (b = 0.058, P = 0.258). Conclusions The present study identified the complex pathway from nutritional status to the activities of daily living through physical function in aged Japanese people requiring long‐term care. These findings suggest that maintaining good nutritional status and nutritional support might delay physical function decline, and prolong the activities of daily living. Geriatr Gerontol Int 2014; 14: 799–805.